Stachys semsurensis (Lamiaceae), a new species from Adıyaman province (Turkey) belonging to section Infrarosularis - Firat, Mehmet (Phytotaxa, 2021)
A new species, Stachys semsurensis (sect. Infrarosularis), is described and illustrated from Adıyaman province, Turkey. From the morphological point of view, it appears to be similar to Stachys cataonica, but it differs in several morphological features including densely covered with short stalked to subsessile glandular hairs in flowering stems, verticillasters congested into ± globose head, calyx teeth lanceolate-subulate, corolla white, tube exserted and nutlets obovoid, greyish-brown, reticulate. A comprehensive description of the new species is provided, including detailed photographs, geographical distribution map, habitat structure and ecology, vernacular name and IUCN conservation status.